2014
DOI: 10.1007/s11663-014-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Non-metallic Inclusions from Molten Steel Using High Frequency Electromagnetic Fields

Abstract: The current work is to investigate the removal of non-metallic inclusions from molten steel using electromagnetic separation under high frequency magnetic fields. A certain amount of aluminum nuggets were added to the molten steel to generate alumina inclusions in the current experiments. A layer of alumina clusters close to the wall of the crucible was observed. Models for the entrapment of inclusions by EM fields were developed, indicating that over 91 pct inclusions were captured within the skin depth (2.31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…The motion of inclusions in the molten steel was calculated by solving the force balance and the trajectory . The inclusions were released from the inlet of the SEN and then moved into the molten steel in the mold.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The motion of inclusions in the molten steel was calculated by solving the force balance and the trajectory . The inclusions were released from the inlet of the SEN and then moved into the molten steel in the mold.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Li et al [12] designed an electromagnetic stirring method and improved inner porosity and composition segregation of steel bloom. Wang et al [13] found that fluid flow induced by electromagnetic force had a close relationship with inclusions of steel based on both the experiment and the simulation results and verified that electromagnetic technology was a feasible and high-efficient method to control inclusions of the molten steel.…”
Section: Introductionmentioning
confidence: 82%
“…Enhancing the cooling rate and introducing physical fields are the two common methods for controlling the MnS precipitation of steel. [9][10][11][12][13] It has been reported that MnS precipitates in the as-cast steel should have a mean length lower than 5lm for to obtain better machinability and mechanical properties. [9] Wang et al [10] found that the percentage of the large MnS with a length over 5lm decreased from 6.2 to 2.6 pct as the solidification condition changed from air cooling to sub-rapid.…”
Section: Introductionmentioning
confidence: 99%
“…The electromagnetic thermal effect can effectively compensate for the temperature of molten steel, reduce the temperature fluctuation of molten steel in the tundish, and achieve the goal of constant temperature pouring with low superheat in the tundish [ 18 , 19 ]. The electromagnetic force effect is reflected in the “pinch effect” generated by the electromagnetic field, which makes non-metallic inclusion particles with small density and poor conductivity move toward the channel wall, where they are finally removed [ 20 , 21 ]. Compared with tundish, and without an induction heating device, the IHT cannot only ensure the outlet temperature but also make use of the temperature difference to generate the density difference to make the molten steel have an upward trend in the distribution room, which is conducive to reducing short circuits and increasing the average residence time.…”
Section: Introductionmentioning
confidence: 99%